Diet intake and endurance performance in Kenyan runners - Christensen, D. L. (Equine and Comparative Exercise Physiology, 2004)
Training and competing at elite as well as sub-elite level requires an optimal functioning of the body. This review looks at the case of the Kenyan runners, who consume a relatively high-quality diet based on vegetable sources with maize and kidney beans as the staple foods. The diet is high in carbohydrate and total protein, but low to borderline in a few essential amino acids. The timing of diet intake - immediately after training sessions - is optimal for skeletal muscle glycogen resynthesis that is enhanced without the help of insulin up to 60 min after cessation of exercise. Whether the total energy intake of the Kenyan runners is adequate is debatable. However, chronic undernutrition is not possible for athletes who engage in daily high-quality and -quantity physical exercise throughout most of the year. It is suggested that Kenyan runners participate in well-controlled, laboratory studies to investigate the quality of local foods and performance, as well as possible physiological adaptation mechanisms among athletes with a high habitual energy turnover.